Two-Phase Image Inpainting: Combine Edge-Fitting with PDE Inpainting (Advances in Applied Mathematics and Mechanics, 2021)
The digital image inpainting technology based on partial differentialequations (PDEs) has become an intensive research topic over the lastfew years due to the mature theory and prolific numerical algorithms ofPDEs. However, PDE based models are not effective when used to inpaintlarge missing areas of images, such as that produced by object removal.To overcome this problem, in this paper, a two-phase image inpaintingmethod is proposed. First, some edges which cross the damaged regionsare located and the missing parts of these edges are fitted by using thecubic spline interpolation. These fitted edges partition the damaged regionsinto some smaller damaged regions. Then these smaller regions may be inpaintedby using classical PDE models. Experiment results show that the inpaintingresults by using the proposed method are better than those of BSCB model and TV model.